Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n029
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation of deck parameters of rotary threshing device

Abstract: The damages of corn grain during threshing depend on many factors, the main of which is timely removal of grain from the threshing chamber what depends on the design of the deck. The functional parameters of the deck in self-propelled combines and stationary threshers used for threshing of seed corn have been studied. Studies of factors affecting the separation process of a mixture consisting of grain and other parts of corn cobs in the threshing chamber were carried out. It has been proved that the shape, siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To determine the Young's modulus, the most scientific interest is the last bend of the curve before the beginning of endosperm deformation, since here the limit of elasticity of the material of the protective fruit shell of the grain is reached. Numerical values of resistance in this area are useful for the Young's modulus calculation by expression (1). The results of the Young's modulus calculation are presented in the form of four intervals of the numerical scale in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the Young's modulus, the most scientific interest is the last bend of the curve before the beginning of endosperm deformation, since here the limit of elasticity of the material of the protective fruit shell of the grain is reached. Numerical values of resistance in this area are useful for the Young's modulus calculation by expression (1). The results of the Young's modulus calculation are presented in the form of four intervals of the numerical scale in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to high yields, corn is distinguished by the presence of a number of subspecies characterized by various mechanical, technological and taste characteristics. In particular, the main industrial subspecies include dent corn, flint corn, sugar corn, flour corn, waxy corn and popcorn [1].…”
Section: Introductionmentioning
confidence: 99%
“…The damage rate and the corn threshing rate can be balanced by reasonably adjusting the concave clearance and the speed of the threshing cylinder, so as to achieve the lowest loss rate. Bakharev D. et al [46] studied the factors influencing the separation effect of mixtures composed of corn kernels and other impurities such as corn cobs. The results suggested that the most influential factor was the threshing time of corn kernels.…”
Section: Effect Of Concave Clearance On Corn Threshingmentioning
confidence: 99%
“…In the process of solving the problem of minimizing the number of macro -and micro-damages to seed grain corn during threshing, an axial-rotary threshing device with pneumatic adaptive deck was theoretically justified and designed, the design and operation of which are described in detail in the source [1].…”
Section: Introductionmentioning
confidence: 99%